2007
DOI: 10.1063/1.2728748
|View full text |Cite
|
Sign up to set email alerts
|

Scanning probe imaging of coexistent ferromagnetism and ferroelectricity at room temperature

Abstract: Room temperature coexistence of ferromagnetism and ferroelectricity in a thin film of a novel material of nominal composition PbTi 0.5 Fe 0.5 O 3 - is probed by standard ferroelectric and ferromagnetic hysteresis loop measurements and by scanning probe microscopy of various kinds.Both magnetic domains and ferroelectric domains are observed in the same spatial region of the material, implying phase coexistence in this system. For both order parameters, sample morphology strongly affects roughness of the domain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 8 publications
(16 reference statements)
1
22
2
Order By: Relevance
“…In the third approach the magnetic ions like Fe, Co, Ni, W, Mn etc. are substituted in ABO 3 type ferroelectric systems [12][13][14][15][16][17][18]. The literature referred between 1 and 14 above are a few examples of each category and not a comprehensive review.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the third approach the magnetic ions like Fe, Co, Ni, W, Mn etc. are substituted in ABO 3 type ferroelectric systems [12][13][14][15][16][17][18]. The literature referred between 1 and 14 above are a few examples of each category and not a comprehensive review.…”
Section: Introductionmentioning
confidence: 99%
“…In past a few years, Fe doped PbTiO 3 has been investigated for its multiferroic properties [12][13][14]. It is observed that the PbTiO 3 matrix shows a solid solubility for concentration of Fe as large as 50 mol% and the compound PbFe 0.5 Ti 0.5 O 3 show a co-existence of ferroelectric and magnetic orders at room temperature, even in the thin film form [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is already reported that the Fe-doped PbTiO 3 and Pb(Sr)TiO 3 show the presence of the ferroelectric and ferromagnetic orders at room temperature. 15,16 Taking into consideration the observations above, it is proposed to investigate Fe-doped SBN systems, such that the ferroelectric transition temperature of the resulting systems occur in the vicinity of room temperature. A possible virtue of these compositions would be a remarkable magnetodielectric coupling, measured in terms of the magneto-capacitance (M c Þ, defined as M c ¼ ½"ðHÞ À "ð0Þ="ð0Þ, where "ðHÞ and "ð0Þ are the dielectric constants in the presence and absence of the applied magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most of the known multiferroic systems are typically antiferromagnetic with transition temperatures below room temperature [1,2]. Recently we have been successful in achieving room temperature multiferroicity in bulk as well as thin films of PbTi 1-x Fe x O 3 system [3,4]. We have also demonstrated the existence of similar properties in bulk and thin films of Bi 0.9-x M x La 0.1 FeO 3 ( M -Tb, Dy) [5][6][7].…”
Section: Introductionmentioning
confidence: 64%